The Relationship between Anxiety, Stress, and Working Memory Capacity - Hanan, Ahmed Ali Al-Fakih (Universiti Malaysia Sarawak (UNIMAS), 2021)
This study designed a quantitative research to identify the relationship between anxiety, stress, and working memory capacity (WMC). The study aims to test the differences between anxiety levels in WMC and the correlation between stress and WMC. The research used a quasiexperiment method where 16 participants were assigned into online assessments to measure anxiety and stress levels, then, they were invited to attend face-to-face task to measure WMC. The study adopted the Beck Anxiety Inventory (BAI) assessment to measure anxiety, the Perceived Stress Scale (PSS-10) assessment to measure stress, and the Operation Span Task to measure WMC. Analysis of the collected data demonstrated that there are no significant differences between anxiety levels in WMC, also, there is no significant correlation between stress and WMC. Overall, the result indicates that anxiety and stress do not influence the capacity of WM. In fact, the research’s findings are opposite to pervious research that have shown a decline in WMC due to high anxiety and stress. For this reason, this experimental research emphasis on the need for further studies of this relationship. However, this study has some limitations in terms of sample size, the variety of WMC task, and the availability of appropriate location.